ANALYSIS OF SIXTH-GRADE STUDENTS’ ABILITY AT SD NEGERI 064976 IN LEARNING THE PAST TENSE - Eva Betty; Dea Yuanita Nasution; Redya E. M Hutabarat; Ruth Aritonang; Dwika Cahyani; Ahmad Zaki Fitrah (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This research seeks to investigate how well sixth graders at SD Negeri 064976 grasp the Past Tense as a component of their foundational English grammar skills. A group of 20 students took part in the lesson and completed a test aimed at evaluating their comprehension of verb alterations and their capacity to form sentences in the past tense. The results reveal significant differences in the students' grasp of the subject matter. Ten percent of the students scored in the high range, forty percent were in the medium range, and fifty percent were classified as low. Those in the high group typically displayed a solid understanding of verb form changes and could accurately create simple past tense sentences. Meanwhile, students in the medium range showed some understanding, but they were inconsistent, particularly with irregular verbs and overall sentence structure. The students classified as low encountered more basic difficulties, such as struggling to differentiate between present and past forms and having a limited vocabulary for building sentences. These findings highlight the necessity for a more organized approach to grammar practice, planned learning sessions, and teaching methods tailored to the diverse readiness levels of students, aimed at enhancing their overall grasp of the Past Tense.